Unfolding workplace skills through Oral Progress Report Activity (OPRA) - Wahiza Wahi,; Azwan Shaiza Nizam,; Normazidah Che Musa, (Penerbit Universiti Kebangsaan Malaysia, 2016)
In line with the changing nature of the workplace, Malaysian higher learning institutions are currently confronted with issues pertaining to graduates’ lack of ability to communicate confidently and fluently in English and to adapt effectively to the requirements of the workplace. This paper deliberates on the dynamic and constructive workplace skills demonstrated by undergraduate students through Oral Progress Report Activity (OPRA), introduced in an English language course. OPRA requires the students to carry out small group discussions in which they present and discuss the progress of their project work in a meeting-like situation. One student leads the group discussion while the others report on the progress of the project. After conducting the OPRA, the students are asked to write on their experiences, feelings and action plans in their reflective journals. Informed by the social theory of learning, this paper explicates the workplace skills involving communication skills, meeting skills and analytical reasoning. Data for this study are drawn from students’ reflective journals and focus group interviews. The findings of the study illustrate that OPRA enhances students’ communication skills, fosters critical thinking skills and increases students’ self-confidence. The findings also show that OPRA encourages them to become critical of their own performance and skills. The implication of this study suggests that the use of pedagogical approach promotes language and communication, and at the same time, emulates workplace skills is important to train students to acquire workplace skills.